KAJIAN INDEKS STABILITAS ATMOSFER TERHADAP KEJADIAN HUJAN LEBAT DI KOTA BITUNG: (STUDI KASUS TAHUN 2020 - 2021) - Kusumawardani, Niken; Azani, Audia Azizah (Pusdiklat BMKG, 2022)
The stability index can be used by weather forecasters to predict heavy rain events. This paper examines the atmospheric stability index for the occurrence of heavy rain in Bitung City, North Sulawesi, during 2020-2021. Stability index data was obtained from the radiosonde of Sam Ratulangi Meteorological Station, Manado. The indexes studied are the Lifted Index (LI), Showalter Index (SI), K-Index (KI), CAPE, SWEAT, and Total-Totals Index (TT). The results show that heavy rain in Bitung occured when the SI, KI, SWEAT, and TT values are in the moderate category. Meanwhile, the LI and CAPE values are less representative in predicting the occurrence of heavy rain in Bitung City. Further research is needed on the relationship between the threshold value of the atmospheric stability index and the weather in Bitung City so that it can be used as a reference for weather prediction.